The effectiveness of fiscal policy in enhancing local investment opportunities, a case study in the state of M’sila - benyettou, rabeh (Journal of Research in Finance and Accounting, 2022)
This study aims to ascertain the reality and effectiveness of fiscal policy in promoting opportunities and attracting domestic investment by highlighting its most important tools represented in fiscal stimulus and its role in attracting investment locally as one of the most important means of improving the investment climate. Through the Algerian State's orientation and commitment to the critical importance of investing in the national economy development of a set of fiscal stimulus as a policy to attract and guide investment with a view to achieving a set of objectives, some of which are conclusions reached through the study as the creation of positions of employment, Eliminating unemployment, creating an internal regional balance, creating wealth, all of which result from the effectiveness of fiscal stimulus in attracting and encouraging investments through local and national support mechanisms and bodies.